2022
DOI: 10.1007/s13138-022-00203-z
|View full text |Cite
|
Sign up to set email alerts
|

Die Rolle des Wissens angehender Mathematiklehrkräfte beim Diagnostizieren schwierigkeitsgenerierender Aufgabenmerkmale. Erkenntnisse aus Eye-Tracking Stimulated Recall Interviews

Abstract: ZusammenfassungDie Schwierigkeit von Mathematikaufgaben wird neben fachlichen Aufgabenmerkmalen auch von instruktionalen Merkmalen bestimmt. Auf der Grundlage eines Modells der Informationsverarbeitung wird angenommen, dass angehende Lehrkräfte ihr Wissen nutzen, um schwierigkeitsgenerierende Aufgabenmerkmale zu identifizieren und hinsichtlich ihrer Schwierigkeit für Schülerinnen und Schüler zu evaluieren. Zur Prüfung dieser Modellannahmen wurden in der vorliegenden Studie drei Studiengruppen bei N = 46 Lehram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 47 publications
1
12
1
1
Order By: Relevance
“…In an eye-tracking stimulated recall interview, participants are asked to retrospectively describe their own thoughts based on a video sequence of their eye movements (Hyrskykari et al, 2008). Visualizing eye movements serves as a memory aid to recall own actions and thoughts and has proven to be an effective method to stimulate reflection of internal cognitive processes (e.g., Schreiter et al, 2022).…”
Section: Eye-tracking For Investigating Students' Mathematical Thinkingmentioning
confidence: 99%
“…In an eye-tracking stimulated recall interview, participants are asked to retrospectively describe their own thoughts based on a video sequence of their eye movements (Hyrskykari et al, 2008). Visualizing eye movements serves as a memory aid to recall own actions and thoughts and has proven to be an effective method to stimulate reflection of internal cognitive processes (e.g., Schreiter et al, 2022).…”
Section: Eye-tracking For Investigating Students' Mathematical Thinkingmentioning
confidence: 99%
“…In an eye-tracking stimulated recall interview, participants are asked to retrospectively describe their own thoughts based on a video sequence of their eye movements (Hyrskykari et al, 2008). Visualizing eye movements serves as a memory aid to recall own actions and thoughts and has proven to be an effective method to stimulate reflection of internal cognitive processes (e.g., van Gog et al, 2005;Schreiter et al, 2022).…”
Section: Eye-tracking For Investigating Students' Mathematical Thinkingmentioning
confidence: 99%
“…Such knowledge is particularly relevant when the diagnostic situation does not require the comparison of students' overall competencies in relation to one another (rank-order assessment) but to assess individual students' level of mathematical competencies relative to a normative competence model and to classify individual students' specific mathematical abilities and misconceptions. Experimental studies showed that directly instructing prospective teachers in specific pedagogical content knowledge improved their accuracy in assessing task difficulties (Ostermann et al 2018) or task features (Rieu et al 2022;Schreiter et al 2022). Consequently, interventions that provide relevant knowledge have the potential to foster prospective teachers' diagnostic competencies effectively even in short interventions during university courses.…”
Section: Providing Instructional Support Through Scaffoldingmentioning
confidence: 99%
“… 2022 ; Schreiter et al. 2022 ). Consequently, interventions that provide relevant knowledge have the potential to foster prospective teachers’ diagnostic competencies effectively even in short interventions during university courses.…”
Section: Introductionmentioning
confidence: 99%